2019
DOI: 10.18406/2316-1817v11n120191234
|View full text |Cite
|
Sign up to set email alerts
|

Sensibility of sugarcane cultivars to pre and post-emergence herbicides

Abstract: Chemical control is used to restrain the attack of weeds on cultivated crops in Brazil; however, the overuse of chemical products can cause damage to the crops. This study aimed to evaluate the phytotoxicity caused by pre-emergence (PRE) and post-emergence (POST) herbicides in sugarcane cultivars and their influence in agronomic and technological traits as well as to verify the existence of correlation between the herbicides effect and the measured traits. The experiment was carried out in a randomized complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Cultivar sensitivity to herbicide treatment is also reported by studies, e.g. (Castro et al, 2019;Al-Latif, 2022). On the contrary, more and more reports (Widianto et al, 2022;Papapanagiotou et al, 2023;Sparangis et al, 2023;Zhu et al, 2023) have indicated the emergence of resistance to pyroxsulam in many common, previously sensitive weeds.…”
Section: Discussionmentioning
confidence: 91%
“…Cultivar sensitivity to herbicide treatment is also reported by studies, e.g. (Castro et al, 2019;Al-Latif, 2022). On the contrary, more and more reports (Widianto et al, 2022;Papapanagiotou et al, 2023;Sparangis et al, 2023;Zhu et al, 2023) have indicated the emergence of resistance to pyroxsulam in many common, previously sensitive weeds.…”
Section: Discussionmentioning
confidence: 91%